2019
DOI: 10.1002/sd.2003
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development and green gross domestic product assessments in megacities based on the emergy analysis method—A case study of Wuhan

Abstract: Globally, cities are generally facing challenges of sustainable development, and this is particularly true in megacities. To reveal the relationship between economy and ecology, green gross domestic product (GDP) represents the ideology and requirements of sustainable development. In this study, emergy analysis theory is introduced to the green GDP accounting system and to a sustainable development evaluation framework using Wuhan City from 1994 to 2015 as a case study. The results show that (a) the green GDP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“…This shows that coordination level between energy subsystem and environmental subsystem is related, as there is a high correlation between energy consumption and environmental degradation (Ashfaq et al, 2016; Esso & Keho, 2016; Wang, Wu, Zeng, & Wu, 2016). Moreover, some scholars found that use of renewable energy has a significant positive impact on environmental improvement (Bilgili, Kocak, & Bulut, 2016; Usman, Alola, & Sarkodie, 2020; Wei, Li, Liu, & Wu, 2018). Paramati, Sinha, and Dogan (2017) used cointegration test model for countries in the N‐11 economies and found that use of renewable energy has not only a positive impact on environmental improvement, but also a positive contribution to economic output.…”
Section: Calculation and Discussionmentioning
confidence: 99%
“…This shows that coordination level between energy subsystem and environmental subsystem is related, as there is a high correlation between energy consumption and environmental degradation (Ashfaq et al, 2016; Esso & Keho, 2016; Wang, Wu, Zeng, & Wu, 2016). Moreover, some scholars found that use of renewable energy has a significant positive impact on environmental improvement (Bilgili, Kocak, & Bulut, 2016; Usman, Alola, & Sarkodie, 2020; Wei, Li, Liu, & Wu, 2018). Paramati, Sinha, and Dogan (2017) used cointegration test model for countries in the N‐11 economies and found that use of renewable energy has not only a positive impact on environmental improvement, but also a positive contribution to economic output.…”
Section: Calculation and Discussionmentioning
confidence: 99%
“…Third, initiatives must be directed toward upgrading the industrial structure, developing the role of the market, increasing the flow of factors between regions, improving energy efficiency, saving energy, and reducing emissions. Moreover, it would be crucial to implement policies to raise the level of urbanization; encourage resource conservation and environmental protection; and, in particular, expand the use of renewable resources and develop industrial system that is energy efficient and low in emissions (Wei, Li, Liu, & Wu, 2020), and improve the allocation of resources (Wang, Hua, & Li, 2019).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Under this background, establishing an effective C&D waste management system has become a globally important research topic, which attracts the interests of not only academia but also local government. Liu, Gong, Wang, Lai, & Zhu, 2019;McCauley, 2015;Wei, Li, Liu, & Wu, 2019;Yuan & Yang, 2020;Zhang et al, 2019). To promote C&D waste management, relevant policies have been implemented in many countries (Ajayi & Oyedele, 2018;Bao & Lu, 2020;Di Maria, Eyckmans, & Van Acker, 2018;Tam & Lu, 2016;Wang, Wu, Tam, & Zuo, 2019;Wu, Zuo, Yuan, Zillante, & Wang, 2020).…”
Section: Introductionmentioning
confidence: 99%